Multiband Laser Action from Organic-Organic Heteroepitaxial Nanofibers. Issue 1632 (4th February 2014) - Quochi, Francesco; Floris, Francesco; Simbrunner, Clemens; Schwabegger, Guenther; Saba, Michele; Mura, Andrea; Sitter, Helmut; Bongiovanni, Giovanni
ABSTRACT: We report successful tuning of laser wavelength from ∼420 nm to ∼600 nm in epitaxially aligned nanofibers grown by periodic deposition of para -sexiphenyl ( p 6P) and sexithiophene (6T) on p -6P/muscovite mica templates. The nanofibers were photoexcited by subpicosecond pulses tuned to the lowest p 6P absorption band, and the emission of 6T, whose coverage was kept in the submonolayer regime, was efficiently sensitized through resonance energy transfer (RET). The 6T lasing was achieved at room temperature with threshold fluences as low as 10 μJ/cm 2 per pulse. Transient photoluminescence measurements, with picosecond resolution, showed that at these pump fluences the decay dynamics of 6T emission is independent of the excitation density, thereby demonstrating the attainment of room-temperature monomolecular lasing from epitaxially oriented 6T submonolayer aggregates. Main lasing properties remained unaltered upon direct photoexcitation of 6T below the p 6P absorption edge.